Connections: percussion experiences beyond the band room - Berglund, Cheryl Hadley (Kansas State University, 2022)
The lessons designed for this project involve taking the percussionist from the band room, into community performance opportunities. Often, music dies for students upon high school graduation because the band room percussionist does not connect those experiences to performances opportunities outside of band. My goal is to promote experiences for percussionists that lead to lifelong engagement in music. Our school district does not have high school musicals for musicians to learn to be a “Pit” musician. I am teaching my percussion ensemble to navigate the rigorous pit percussion set ups, fast transitions, and unpredictability of being an accompanist for musicians on stage. The end goal is these students will be ready to perform when called upon to perform and engage outside of school music experiences. My career focuses on designing music programs, supporting the faculty who serve the students and teaching percussion. The coursework provided in this program is enhancing my effectiveness as a leader and teacher resulting in reaching additional students through innovative ideas and sustaining the current students with renewed passion forteaching. As I collect my annual statistics each year, I am reminded that my studies at Kansas State University are creating a story in music education for Austin Minnesota. “Effective communication of a story is key, perhaps the key, to leadership. Why? Because stories are the real thing. They are how we learn, how we visualize what can be. “Don’t just present them with numbers. Tell the story” (Shoop 62). In World Pedagogy, I designed a project that turned into 1200 elementary students studying and presenting Korean Folk Songs with Dr. Soojin Lee. I also broke out of the classic western box during the course and created Orange Haze, a rock band project complete with a logo, and community performances. The lessons designed for being a pit musician were designed in Advanced Rehearsal Techniques. I focused my teaching skills by using philosophies of Eisner who believes the benefits of the arts are more than the art itself and merging educational theories like growth mindset which allows students, “NOT YET” in achievement spectrums rather than failure. A self-imposed graduate requirement was to improve my performance skills. After a 17-year hiatus from marimba, I took the stage with a newly formed group named Tryptich. My students were able to watch me achieve goals, hear me tackle difficult passages and see me perform substantial music. The coursework provided during my graduate work at Kansas State University has led to confidence while leading my community, teaching with more focus and intentionality, and becoming a whole musician again.
Keywords: Percussion; Pit percussion; Orchestra pit